Halal cosmetics usage among millennials: social influence as mediator - Husin, Nor Azilah; Mariyanti, Eka; Saad, Mazni; Lukito, Hendra; Maulad Hamzah, Aishah (European Publisher Limited, 2022)
These days cosmetics have gotten mainstream among all, including the millennials around the globe; however, the mindfulness for halal cosmetics agents is powerless. Inferable from the expanding interest for halal products on the world's market, numerous Muslim shoppers feel dubious and unconfident that the sold items are shariah compliant. Be that as it may, very few organizations in Malaysia can deliver beauty care products, causing Muslims who pick makeup to have constrained options. This study proposes using a mediation model that links individual factors, religiosity, and halal cosmetics usage via social influence. A quantitative method and probability sampling technique using random selection. A survey was conducted on 161 university students from both public and private universities. SmartPLS was used as the structural equation modelling approach to perform the analysis. The findings showed that religiosity has no significant influence on halal cosmetics usage among millennials. Interestingly, the social influence mediates the relation between religiosity and halal cosmetics usage. Though the individual factor directly affects halal cosmetics adoption, social influence's indirect effect has shown otherwise. The theory of self-determination among millennials prevails. The implication of this study will help shed light on the understanding of the present market circumstances of the cosmetics business in Malaysia, which is in line with Sustainable Development Goal 3 to ensure a healthy life and promote well-being for all at all ages.